About the author of “Wanderings around the land of Uryankhay” after 115 years - Mongush, Zoia M. (The New Research of Tuva, 2010)
Article describes the life of A. V. Potanina - the first Russian woman who has travelled around Tuva in 1876 and 1879. The material is based on the rare and unique travel papers.